Temperature Distribution Fire Furnaces: Experiment & Numerical Approach - Santosa, Irfan; Farid, Ahmad; Hendra Hermawan, Okky; Wibowo, Agus (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
A fire furnace is a combustion tool, that has a function to produce sufficient heat for combustion purposes. The even distribution of temperature can accelerate the combustion process. This research aims to investigate the temperature distribution in a fire furnace, both experimentally and numerically, to analyze temperature distribution during combustion. The air spray speed in the stove will be varied at 1.36 m/s, 1.45 m/s, and 1.53 m/s. The research method involves experimental observation and numerical simulation using Computational Fluid Dynamics (CFD). The results showed an air jet speed of 1.36 m/s, the experimental and numerical temperature values are 619.2 °C and 621.5 °C with a percentage error of 0.37%. For an air jet speed of 1.45 m/s, the temperatures obtained in the experiment and simulation are 637.3 °C and 642.5 °C with an error percentage of 0.81%. Finally, at an air jet speed of 1.53 m/s, the experimental and numerical temperatures are 659 °C and 670.9 °C with an error percentage of 1.80%. The research concludes that both experimental and numerical methods provide a consistent and accurate temperature distribution.